Myths about fingerprint evidence: Basic facts countering miscarriage of justice. Part 1 - Mansour, Saleh; Zade, Shital; Rohatgi, Shipra; Oklevski, Slobodan (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The long practice of fingerprint science is accompanied by confusing thoughts affecting the interpretation of the fingerprint evidence recovered from a crime scene, and, consequently, prosecutors and judges’ decisions as well. However, despite the tremendous scientific and technological developments relating to fingerprint enhancement, processing, and usage, which clarify precise facts regarding the influence of deposition circumstances, substrate, light, air, temperature, and time factors on fingerprint secretions, misconceptions about fingerprints are still widespread within the law enforcement and judicial system. This problem prevents the proper usage of fingerprints in fighting crimes and supporting the justice system by strong physical evidence. This study aims to highlight some scientific facts about fingerprints as well as a new approach and reconceptualization of fingermarks as a tool for crime scene investigation and training. The article discusses twenty-four myths about fingerprints – part 1 covers ten of them and part 2 discusses the other fourteen.
Keywords: starzenie się odcisków palców; składniki; anatomia skóry; techniki przetwarzania; delikatne powierzchnie; wrażliwość odcisków palców; interpretacja dowodów; metodologia ACE-V